2008
DOI: 10.1002/art.23532
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term followup of temporomandibular joint involvement in juvenile idiopathic arthritis

Abstract: Objective. Temporomandibular joint (TMJ) involvement is a frequent feature in cross-sectional prevalence studies among patients with juvenile idiopathic arthritis (JIA). In this followup study, patients were reviewed after 5 years to study the course of TMJ involvement in relation to disease characteristics. Methods. Children with JIA from a previous study on TMJ involvement were included. A rheumatologic evaluation including the 6 parameters of the JIA core set and an orthodontic evaluation including an ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 17 publications
4
55
1
16
Order By: Relevance
“…69 It is well known that symptoms and clinical signs of TMJ involvement may be subtle, making imaging an important diagnostic tool. [75][76][77] Some CBCT studies of patients with JIA are available. A clinical evaluation according to the research diagnostic/TMD criteria 78 revealed only a few of the patients with JIA with TMJ bone abnormalities on CBCT.…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…69 It is well known that symptoms and clinical signs of TMJ involvement may be subtle, making imaging an important diagnostic tool. [75][76][77] Some CBCT studies of patients with JIA are available. A clinical evaluation according to the research diagnostic/TMD criteria 78 revealed only a few of the patients with JIA with TMJ bone abnormalities on CBCT.…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…The reported frequency of TMJ involvement ranges in the literature from 17% to 87%, depending on the population investigated, the subtypes represented, and the radiologic method by which involvement is diagnosed. [5][6][7][8][9][10][11][12][13][14] Only one study reported the incidence of TMJ involvement in all subtypes of JIA. 6 The most important site of growth of the mandible in the vertical and sagittal direction is located on the articular surface of the condylar head.…”
Section: Introductionmentioning
confidence: 99%
“…6 A drastic decrease in the prevalence of OPT alterations was observed during follow-up. 6,7 The aim of this survey was to study how the course of condylar alterations can influence the craniofacial skeleton in patients with JIA over a 5-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Pedersen et al [30] performed repeated TMJ MRI in 15 JIA patients prospectively 4 times within 2 years and found that nearly all had inflammatory signs at some point in time. Interestingly, on long-term follow-up improvement as well as worsening of the condylar shape have been demonstrated [33,34]. Why a presumably undulating inflammatory process will lead to progressive destruction in some patients but allows condylar remodelling in others remains unclear so far.…”
Section: Discussionmentioning
confidence: 99%